Mamalia Kecil Terestrial di Gunung Kerinci dan Gunung Tujuh dalam Kawasan Taman Nasional Kerinci Selat (TNKS) - Karmelia Kontesa; Wilson Novarino; - Rizaldi (Jurnal Biologi Universitas Andalas, 2014)
An inventory of terrestrial small mammal was conducted in January and August 2013 in the Mt. Kerinci and Mt. Tujuh. The mammals were captured using snap and pitfall traps with a total effort of 650 trap nights. This study found 10 species of small mammals that belong to 4 families and 3 orders. Some species were found in both Mt. Kerinci and Mt. Tujuh. Similarity index of Sorensen between the two locations was 42%. Those species inhabited in the two locations were Hylomys suillus, Lariscus insignis and Niviventer rapit. Key words: Mt. Kerinci, Mt. Tujuh, small mammal, terrestrial.